Motivational interview and scales used to assess the degree of motivation for treatment in drug abuse patients (Archives of Clinical Psychiatry, 2005)
OBJECTIVE: To identify and review tools used in specialized services to explore aspectos of motivation as a predictive factor of treatment outcome in drug-abusing patients. METHOD: Comprehensive literature review of scales used to assess the degree of motivation. RESULT: Four scales to evaluate stages of behavioural change related to motivation were identified and described, together with their associated psychometric properties - Rhode Island Change Assessment Questionnaire (URICA), Stages of Change Readiness and Treatment Eargness Scale (SOCRATES), Treatment Motivation Questionnaire (TMQ), Readiness to Change Questionnaire (RCQ); The first two have Portuguese validated versions. CONCLUSION: Motivacional theory has been regularly studied in the last decade, allowing the definition of pragmatic evaluation parameters in scales with validity and reliabilities that vary from good to excellent.